1997
DOI: 10.1037/0894-4105.11.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Generation effects and source memory in healthy older adults and in adults with dementia of the Alzheimer type.

Abstract: Recognition and source memory were explored in healthy older adults, adults diagnosed with very mild dementia of the Alzheimer type (DAT), and adults diagnosed with mild DAT. Two sentence-completion tasks were used. In Task 1, half of the sentences were completed (clozed) by the participant, and half by the experimenter. In Task 2, half were participant clozed, and half were participant read (already clozed). Recognition of the cloze words and accuracy of categorizing them as participant generated or experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 37 publications
5
59
0
1
Order By: Relevance
“…Thus, we can suggest that, unlike normal elderly subjects who only have difficulties completely suppressing TBF items from working memory but clearly distinguish between TBF and TBR items (since they produced no more intrusions than young subjects), AD patients have additional difficulties inhibiting the production of the TBF items. We can hypothesize that the memory traces for TBF items are as strongly activated as those of the TBR items and that, due to the source memory deficit presented by these patients (e.g., [79]), the presentation of the recall cue triggers the production of any activated item. Indeed, an influence of source memory failures on the performance in verbal working memory tasks was previously described [see 54] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can suggest that, unlike normal elderly subjects who only have difficulties completely suppressing TBF items from working memory but clearly distinguish between TBF and TBR items (since they produced no more intrusions than young subjects), AD patients have additional difficulties inhibiting the production of the TBF items. We can hypothesize that the memory traces for TBF items are as strongly activated as those of the TBR items and that, due to the source memory deficit presented by these patients (e.g., [79]), the presentation of the recall cue triggers the production of any activated item. Indeed, an influence of source memory failures on the performance in verbal working memory tasks was previously described [see 54] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that item memory and source memory respond similarly to generation, the most parsimonious conceptualization of memory would suggest that item and source memory do not tap distinct systems. However, there are data in the literature that suggest that in comparison with item memory, source memory can be disproportionately disrupted (e.g., Multhaup & Balota, 1997). Thus, a more prudent view is that item memory and source memory show overlap, but not complete over- lap, in their underlying processes (see Johnson et al, 1993, for a complete discussion).…”
Section: Discussionmentioning
confidence: 99%
“…In other paradigms, DAT individuals have shown less awareness of source than have healthy older adults (Multhaup & Balota, 1997), who in turn typically have shown worse source memory than have healthy younger adults. In a longer version (Marsh et al, 2003) of the current procedure, researchers found that younger adults were very good at knowing that facts had been read in the stories.…”
Section: Discussionmentioning
confidence: 99%